ANALISIS PENGENDALIAN INTERNAL ATAS PERSEDIAAN PADA PERUM BULOG DIVRE SULUT - Biga, Julian; Ilat, Ventje; Elim, Inggriani (Universitas Sam Ratulangi, 2013)
Supply constitutes a firm Current Assets, that its amount is material and constituting one of essential factor in corporate activity supporter. That is why it has to be done by a good internal control tosecure supplies of acts of fraud,deviation and demage. At one point, the purpose of this research is to know what is the internal control that did by Perum Bulog Divre Sulut in order to get a clear picture about the internal control of rice supply that is applied was effective or not. The method that is utilized in this research is qualitative descriptive method, this method will figure the internal control of supply in Perum Bulog Divre Divre Sulut. From the results of this research is concluded that the rice supply internal control by Perum Bulog Divre Sulut was effective, where there is a separation between functions that is concerning the rice input and output. The monitoring of rice supply is also been done everyday. But, the Perum Bulog Divre Sulut still need to fix their weaknesses in its physical protection with assembling CCTV camera at the storehouse to create an effective internal supply observation.